Performance of Four Step Engine Generator Set with Oxy-Hydrogen (HHO) Fuel from Water Electrolysis Process Using Vacuum Valve Carburator - Theodorus Rendy Prasetya; Lathifa Putri Afisna; Devia G.C. Alfian; Rizky Faesal Sadikin (UIR PRESS, 2022)
Alternative energy sources are required to lessen the environmental impact brought on by the usage of fossil fuels as a result of rising energy demand and rising fossil fuel use. One of the fuels that can be utilized to power generator sets is oxy-hydrogen gas. Oxy-hydrogen gas can be obtained from the electrolysis of water using environmentally friendly energy sources. This study aims to determine the effect of the use of oxy-hydrogen gas from the electrolysis of water as an alternative fuel, to find the performance parameters of the generator set engine using oxy-hydrogen fuel, to compare the performance of the generator set engine with oxy-hydrogen gas fuel with other fuels like pertalite fuel and a mixture of oxy-hydrogen gas and pertalite. The study used a 4 stroke gasoline engine generator set mounted with a vacuum valve type carburetor with a load of 1000 watts which is commonly used. From the results of the study, the performance parameters of the generator set were obtained using oxy-hydrogen fuel. The parameter value when the load is 1000 watts, the effective power of the generator is 1.035 kW, the torque value at 3.297 Nm, specific fuel consumption is 0.3658 kg/kW.hour, the thermal efficiency value is 12.05% and the average effective pressure value is 184.06 kPa.